2014
DOI: 10.1007/s11010-014-2163-7
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of β-catenin with Notch intracellular domain in colon cancer: a possible role of Notch1 signaling in activation of CyclinD1-mediated cell proliferation

Abstract: The Wnt and Notch1 signaling pathways play major roles in intestinal development and tumorigenesis. Sub-cellular localization of β-catenin has been implicated in colorectal carcinogenesis. However, the β-catenin and Notch intracellular domain (NICD) interaction has to be addressed. Immunohistochemistries of β-catenin, NICD, and dual immunofluorescence of β-catenin and NICD were analyzed in colorectal tissues and HT29 cell line. Moreover, real-time PCR analysis of CyclinD1, Hes1 and MUC2 was done in HT29 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“…Intriguingly, the favorable impact of high JAG1 expression on clinical outcome was particularly evident in tumors with negative nuclear b-catenin expression, which supports the well-described importance of the interconnection of the Wnt/b-catenin pathway (Balint et al 2005, Crosnier et al 2006, Wang et al 2009a, Yamamizu et al 2010, Kwon et al 2011, Peignon et al 2011, Kim et al 2012, Ravindran & Devaraj 2012, Gopalakrishnan et al 2014.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Intriguingly, the favorable impact of high JAG1 expression on clinical outcome was particularly evident in tumors with negative nuclear b-catenin expression, which supports the well-described importance of the interconnection of the Wnt/b-catenin pathway (Balint et al 2005, Crosnier et al 2006, Wang et al 2009a, Yamamizu et al 2010, Kwon et al 2011, Peignon et al 2011, Kim et al 2012, Ravindran & Devaraj 2012, Gopalakrishnan et al 2014.…”
Section: Discussionsupporting
confidence: 67%
“…In particular, the link between Notch and Wnt/b-catenin signaling has been investigated in human development (Balint et al 2005, Crosnier et al 2006, Yamamizu et al 2010, Peignon et al 2011, Ravindran & Devaraj 2012, Gopalakrishnan et al 2014, and either additive or opposing effects have been reported, depending on the respective tissue and interfering factors (Kwon et al 2011, Kim et al 2012. Interestingly, Notch pathway activation has also been related, either alone or together, to Wnt/b-catenin activation and p53 deletion, to the epithelial-mesenchymal transition that is involved in the initiation of metastasis (Wang et al 2009a, Espinoza & Miele 2013, Chanrion et al 2014, and to resistance to treatment (Wang et al 2009b, Yao & Qian 2010, Ma et al 2013, Yoon et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, any type of occurring disorder involving regulatory factors will lead to abnormal cell proliferation, thus inducing tumor formation and progression. Cyclin D1 can be combined with cyclin-dependent kinase 4 in the cell cycle to promote cell cycle progression, and therefore, is regarded as a type of proto-oncogene (28). Cyclin D1 protein expression is significantly correlated with colon cancer histology, presence of lymph node metastasis and staging, and colon cancer progression and metastasis (29).…”
Section: Discussionmentioning
confidence: 99%
“…We also identified increased expression of the connective tissue growth factor gene (Ctgf), which encodes a trophic factor known to stimulate NotchR and Wnt signaling (41), and the parkin2 gene (Park2), which is involved in mitophagy (42). The most downregulated genes included several cell cycle genes, encoding cyclin D1 (Ccnd1), cyclin A2 (Ccna2), and cyclin-dependent phosphatase (Cdc14a), all of which are known to be regulated by NotchRs or NotchR signals (43)(44)(45); a gene encoding a suppressor of cytokine signaling 2, a regulator of Jak-Stat signaling (46); one Wnt receptor gene (Fzd6) (47); and an insulin-like growth factor binding protein gene (Igfa1) (48). Several other genes tested were not significantly changed.…”
Section: Resultsmentioning
confidence: 99%